Audiovisual Based Interventions for Promoting Language and Speech Development in Children: A Scoping Review - Apriliana Widiastuti; Meira Erawati; Sri Padma Sari (GLOBAL HEALTH SCIENCE GROUP, 2026)
Language stimulation is essential for children’s language development. Advances in technology have promoted the use of audiovisual tools in language development interventions. Numerous studies have explored technology based language interventions, existing literature lacks an integrated overview of how different audiovisual tools contribute to children’s language outcomes. This review aims to identify and categorize various audiovisual interventions that have been employed in previous studies to enhance children's language abilities. A scoping review methodology was applied, following the PRISMA 2020 protocol. Articles were sourced from three databases—Scopus, PubMed, and EBSCO—based on the inclusion criteria of open-access, full-text, English-language articles published between 2020 and 2025, focusing on language development interventions in children aged 2–12 years. A total of 7.313 records were identified, and 13 studies met the inclusion criteria for analysis. The review identified three main types of audiovisual interventions: Socially assistive robots, augmented reality, and mobile assisted language learning. These interventions have been shown to improve various aspects of children's language abilities, including articulation, vocabulary, and learning engagement. Audiovisual-based interventions have the potential to support children's language development. The findings of this review may serve as a basis for educating parents and healthcare professionals about children's language development.